Restrukturisasi Pembiayaan UMKM Terdampak Pembangunan Tol Trans Sumatera Perspektif Maslahah - Arya Winata; Muhammad Ramadhan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The construction of the Trans-Sumatra Toll Road provides macroeconomic benefits through enhanced connectivity and logistical efficiency. However, it generates structural negative impacts on Micro, Small, and Medium Enterprises (MSMEs) along the old road corridors. This study aims to analyze the impact of the Trans-Sumatra Toll Road development on MSME financing in Pasar Bengkel, Perbaungan Subdistrict, Serdang Bedagai Regency, and to examine the justification for financing restructuring for affected MSMEs from the maslahah perspective. Employing a juridical-empirical approach, primary data were collected through in-depth interviews with 10 MSME actors, while secondary data were drawn from legal regulations and related literature. Findings reveal an average turnover decline of 40–50%, liquidity constraints, and heightened risk of non-performing financing. None of the respondents received effective restructuring, such as margin relief or temporary tenor extensions. From the maslahah perspective, restructuring is justifiable as a means to prevent harm (dar’ al-mafāsid) and preserve wealth (hifẓ al-māl), consistent with Sharia principles in Al-Baqarah verse 280. The study concludes that expanded regulations and strengthened maslahah-based policies are essential to align infrastructure development with economic justice for MSMEs.